Kunci Mahathir : kegemparan baru, UMNO tawan Kelantan, PAS gugat Terengganu - Sharifuddin Ab. Rahman (Kuala Lumpur : Tinta Merah, 1995)
Politics and government in Kelantan and Terengganu; political competition between UMNO and PAS in Kelantan and Terengganu, Malaysia.
In Malay.
Keywords: United Malays National Organisation; Parti Islam SeMalaysia; Kelantan -- Politics and government; Terengganu -- Politics and government